Hubungan Distres dengan Kadar HbA1c dan LDL pada Pasien DM Tipe 2 - Tyas, Asih; Subiyanto, Paulus; Kristanti, Fittriya (PSIK FKKMK UGM, 2025)
Background: Diabetes mellitus (DM) type 2 is a metabolic condition that requires long-term and strict management. In addition, HbA1c level is a determinant for the level of blood sugar in certain time. Furthermore, for patient with DM, high levels of distress can affect glycemic control, HbA1c, and lipid profiles, including Low-Density Lipoprotein (LDL).Objective: To determine the correlation between distress level with HbA1c and LDL levels in patients with type 2 DM at the Panti Rapih Hospital Polyclinic.Method: This research was quantitative and correlational analytical research with cross-sectional design. The study population was 194 patients with type 2 DM who used Oral Hypoglycemic Drugs (OHO) from April, 15th to 20th 2024. Consecutive sampling technique was used to choose 131 respondents diagnosed with type 2 DM who were treated at the Panti Rapih Hospital Polyclinic. Data was collected through Diabetes Distress Scale (DDS) questionnaires to see the correlation between distress level with analysis of HbA1c and LDL levels. The Spearman correlation test was carried out to determine the correlation between distress levels with HbA1c and LDL levels.Results: The result of the Spearman correlation test showed that the correlation between distress levels and HbA1c levels had coefficient of 0,075 and p-value of 0,393. Meanwhile, the result of data analysis between distress levels and LDL levels had a correlation coefficient of -0,019 and a p-value of 0,826.Conclusion: There is no significant correlation between the level of distress with the levels of HbA1c and LDL in Type 2 DM patients at the Panti Rapih Hospital Polyclinic.INTISARILatar belakang: Diabetes Melitus (DM) tipe 2 adalah kondisi metabolik yang memerlukan manajemen jangka panjang dan ketat. Kadar HbA1c merupakan penanda tingginya glukosa dalam darah pada periode waktu tertentu. Pada pasien DM, tingkat distres yang tinggi dapat memengaruhi kontrol glikemik HbA1c dan profil lipid, salah satunya Low-Density Lipoprotein (LDL).Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan tingkat distres dengan kadar HbA1c dan LDL pada pasien DM tipe 2 di Poliklinik Rumah Sakit Panti Rapih.Metode: Penelitian ini merupakan penelitian kuantitatif analitis korelasional dengan desain cross sectional. Populasi penelitian ini sebanyak 194 pasien DM tipe 2 yang menggunakan obat hipoglikemik oral (OHO) dalam periode 15-20 April 2024. Sejumlah 131 responden dengan diagnosis DM tipe 2 yang berobat di Poliklinik Rumah Sakit Panti Rapih, dipilih dengan teknik consecutive sampling. Data dikumpulkan melalui kuesioner Diabetes Distress Scale (DDS) untuk melihat hubungan tingkat distres dengan analisis kadar HbA1c dan LDL. Uji korelasi Spearman dilakukan untuk mengetahui hubungan tingkat distres dengan kadar HbA1c dan LDL.Hasil: Uji korelasi Spearman menunjukkan hasil data antara tingkat distres dan kadar HbA1c dengan koefisien korelasi 0,075 serta nilai p-value 0,393. Sementara itu, hasil analisis data antara tingkat distres dan kadar LDL dengan koefisien korelasi -0,019 dan nilai p-value 0,826.Simpulan: Tidak ada hubungan yang signifikan antara tingkat distres dengan kadar HbA1c dan LDL pada pasien DM Tipe 2 di Poliklinik Rumah Sakit Panti Rapih.